Obstacle and Driving Factors of Ciliwung River Revitalization and Community Acceptance of The New Land Use - Ayu Puspito Sari, Deffi; Yuri Ramadhonah, Ristianti; Innaqa, Suci; Sugiana, Astrid; Erwin Irawan, Dasapta; ., Ratnadewi; ., Supriyono; Harmanto, Dani (International Journal of Engineering and Technology, 2018)
This research was conducted to understand community acceptance of the new land use and to reveal the obstacles and driversâ€™ factors of the river revitalization process. Using questionnaire and interview to 100 respondents in Kampung Pulo, the result shows that 98% of respondents are agree with the revitalization, 62% of respondents stated that the new land use is good. 82% of community expectations for the new land use as green open space, 11% of community expectations for the new land use as a place for cultural show, 5% of community expectation as a recreation park/playground, and 2% of responded expect the new land use as place for sport. It can be concluded that green open space is the most expected new land use. Plants and trees are still limited so that the area is hot and arid. However, there are many obstacles and driving factors in Ciliwung river revitalization, such as the promise of replacing land that occupied by the displaced people, free placement at the new place (Rusunawa Jatinegara), and the demonstration also the mass action during the evictions. Besides the obstacles, there are also driving factors of Ciliwung river such as its widened area, flood control, and the creation of the new road access. There is a model that can be applied in the landscape or urban planning area study with reference to the stages of: residents settlement on the banks of the river, clearance of settlements, develop green open space in cleared areas, and safe guarding of the new land use. This research model can be applied in other areas using the same variables, with the assumption that the area has the same river morphology, urban slum and densely populated areasÂ Â